JAKE SULLY’S EFFORTS IN PRESERVING NATURE AGAINST HUMAN’S GREED IN JAMES CAMERON’S “AVATAR” - WIJAYA, MELISSA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Nature has an ecological system that must be managed by all of human beings.Unfortunately, people are careless about their duties which then causes manyenvironmental destructions. This research deals with man‟s efforts to save thenature as reflected by Jake Sully, the main character of Avatar movie. Avatar tellsabout a place in outer space named Pandora, it is a spot of unobtanium, grey rockscost twenty million dollars/kg. There is a group of people who want to destroyPandora to get the unobtanium. Because of that reason, the aim of this research isto reveal Jake Sully*s efforts to save the nature. The theoretical framework isderrived from the idea of ecocriticism.In conducting this research, there are three steps taken as the methodology.First is deciding object material, Avatar movie. Second is analyzing andinterpreting the texts. The material object will be analyzed by enclosing the screencapture and the script or dialogue related to the topic of discussion. The last isdrawing the conclusion.This research finds that the destruction of Pandora happens because of humans‟greed. People destroy the nature to get their purposes which causes many negativeimpacts, because Jake Sully falls in love with Pandora, it becomes his reason to dosome efforts. There are Jake Sully*s efforts to preserve Pandora such as betrayingthe mission, preventing the military agression by stopping the tractors whichdamage the trees, and leads the war against military agression.In conclusion, Jake Sully has become an agent of change to create a betterworld by preserving Pandora from humans‟ greed. He is aware that man andnature should live in harmony. The further researchers can analyze Avatar moviethrough another perspective such as semiotic criticism to analyze the signs in themovie. Keywords: Jake Sully*s efforts, preserving nature, human‟s greed, Avatar.